A comparison of methods for the measurement of CO2 and CH4 emissions from surface water reservoirs: Results from an international workshop held at Three Gorges Dam, June 2012. (28th January 2015) - Zhao, Yan; Sherman, Bradford; Ford, Phillip; Demarty, Maud; DelSontro, Tonya; Harby, Atle; Tremblay, Alain; Øverjordet, Ida Beathe; Zhao, Xinfeng; Hansen, Bjørn Henrik; Wu, Bingfang
Abstract: Fluxes of carbon dioxide (CO2 ) and methane (CH4 ) from hydroelectric and water supply reservoirs are receiving increasing attention around the world with a number of research groups having undertaken measurements of these emissions across a range of lakes and reservoirs located in different climates and landscapes. The use of floating chambers (aka flux chambers) is the most common technique for direct measurement of these fluxes. However, the relative performance of different measurement systems, especially different chamber designs, is not well documented. We report the results of an international workshop held in June 2012 at Three Gorges Dam, China, to compare measurements performed by four groups with extensive chamber monitoring experience: the Chinese Academy of Science (China), CSIRO (Australia), SINTEF (Norway), Hydro‐Québec/Environnement Illimité (Canada). A fifth group, Eawag (Switzerland), performed hydroacoustic surveys to detect ebullition in the water column. We recommend CH4 as a more suitable trace gas for comparing methodologies due to its relative stability in the surface layer of the water column, for example, it is not subject to significant diurnal changes due to photosynthesis and respiration. Measured fluxes agreed to within 20% between the four teams suggesting that the shape and dimensions of the floating chambers and the chamber gas flow rates (i.e., chamber residence time) did not have an appreciable systematic effect on the measured fluxes for the relatively low wind speeds prevalent at the reservoir. The CO2 and CH4 fluxes measured during the workshop agree well with previous measurements in Three Gorges Reservoir.